Testing mode, construct validity, and the effects on testing outcomes - Buško, Vesna (2009)
The paper deals with some aspects of construct validity mainly pertaining to performance-based assessment. The means to identify unique sources of true test score variances will be presented and discussed in the context of psychometric test theory and its particular models, and demonstrated through the structural equation modeling framework. The presentation will focus on prospects of use of information and communication technology in psychological testing practices, pointing also at basic conditions required to facilitate decision-making and bring about desired changes in the assessment. In view of ever-increasing technological advancements the shift in testing mode seems to be inevitable. It may be worth noting that this venture, whenever admitted, is relevant to the extent that it contributes to the major objectives and purposes of the assessment. Having these facts in mind, the present paper aims to outline a range of requirements and challenges related to this major change in the testing mode practices. The reflections on benefits of implementing information technology in the assessment processes and likely obstacles to transition in testing mode practices will be exemplified by recent data from several large-scale testing projects.
Projekt MZOS
ENG